Peningkatan Kualitas Layanan untuk Meningkatkan Minat Konsumen di Rest Area KM 49A Tol Bakauheni Palembang - Setiawan, Bintang; Defrizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to evaluate the quality of service at Rest Area 49A Bakauheni Palembang Toll Road and analyze the efforts made by the Rest Area owner to improve service quality, with the hope of stimulating consumer interest in stopping by. The research method applied is qualitative with an interview approach. The theoretical basis used includes aspects of marketing management, service quality, and interest in visiting rest areas. The research results show that the quality of service at Rest Area 49A includes extensive facilities, such as parking lots, worship facilities, and clean and comfortable food stalls. The services provided by employees include quick response to customer complaints, attention to customer needs, as well as friendly, polite, and polite service. In terms of security guarantees, the Rest Area protects its visitors. Rest Area owners make various efforts to improve service quality, including increasing security, increasing comfort, and improving facilities to ensure customer satisfaction.